ROAD TRAFFIC AS A SOURCE OF NOISE POLLUTION (CASE STUDY: TRSTENIK MUNICIPALITY) - Ljiljana Pecić; Predrag Pravdić (BizInfo)
Noise is a known pollutant of the environment, especially noise coming from road traffic. This paper describes the study of noise levels at 4 locations in the town of Trstenik, which was carried out during the 2017. Based on the obtained results, appropriate analyzes were carried out and recommendations for reducing the noise level to the allowed limits are given.